Foreign Policy Of Russia In The Eighteenth Century: Goals And Results Of Wars - Matveeva, Elena (2018)
This problem being discussed is important today because the issue of the results of Russia's foreign policy in the eighteenth century is still debatable in contemporary Russian historiography. This discussion is connected with the preservation in the minds of Russian society of an ambivalent attitude towards the territorial growth of the Russian Empire in this century. A part of the society welcomes this growth, which has allowed Russia to reach the seas. Another part of the society indicates the great human and financial losses that the country has suffered as a result of expansion. A goal of the article is to relate the goals set by the Russian elite to the wars and the results achieved. The leading approach to the study of this problem has become a general scientific method of analysis and synthesis. The article describes the goals that the rulers of Russia set for themselves before the beginning of various wars. It characterizes the results of those wars. It assesses the effectiveness of the wars based on the correlation of the results, which were achieved, with the goals set. It reveals the trends in the development of this effectiveness. The materials of the article can be useful for clarifying the ideas about the foreign policy of the Russian Empire in the eighteenth century.